Prevalence of eating disorder attitudes among men and women with exercise dependence symptoms: a non-athlete population study - Elaine Fernanda da Silva; Aliane Ramalho da Silva; Amarilis Dias da Silva; Gustavo Rodrigues Pedrino; Daniel Alves Rosa (Colégio Brasileiro de Ciências do Esporte, 2013)
The present study sought to describe the prevalence of Secondary Exercise Dependence (ScED, i.e. eating disorders attitudes along with exercise dependence symptoms) may differ between men and women in a broader exercising population. In this study, 174 regularly exerciser, aged 18-62 years old, who were invited to respond the Exercise Dependence Scale (EDS) and the Eating Attitudes Test (EAT-26). There were more women than men with ScED. However, only men in the sample presented exercise dependence symptoms without eating disorders attitudes. Eating disorders may or may not exist in those who are exercise dependent in the broad exercising population, although there is a higher prevalence of ScED in women than men.